Determinants of Smart city commitment among citizens from Bahía Blanca, Argentina - Alderete, Maria Veronica (2021)
This paper aims to examine the determinants of smart cities activities across individuals from Bahía Blanca, Argentina. Literature has identified different factors explaining citizens’ commitment with smart cities, such as education, age, labor condition; and other more subjective factors such as trust and awareness about the smart city concept. A critical determinant of smart commitment is e-readiness or digital readiness; that is, the level of preparedness to properly exploit internet opportunities such as e-government and e-commerce. To achieve this goal, we used a survey conducted on 97 citizens following Moderniza Bahía Facebook from Bahia Blanca, Argentina. By estimating a structural equation model, we obtained that higher levels of ICT use are associated with higher levels of smart city commitment, and that higher awareness of the smart city concept relates to higher levels of smart city commitment. Demographic factors such as age and labor condition also explain ICT use. These insights are useful for city stakeholders and policy makers to design properly smart city policies and strategies for citizen engagement.